The investment in white benevolence in a small Karoo town - Fourie, Gina (Department of Sociology, 2014)
This minor dissertation is based on fieldwork conducted for the Institute for Intercultural and Diversity Studies (iNCUDISA) at the University of Cape Town's Rural Transformation Project. The focus is on the investment in 'white benevolence' in a small Karoo (Northern Cape) town and in ways that white residents present themselves, and position themselves discursively, as benevolent whites. Loosely located in social constructionist and postmodernist paradigms, this piece of work also attempts to illustrate how lived experience and the situatedness of subjectivity impact on the research experience and the subjectivity of the 'researcher.' Ultimately, it is posited that if we are interested in the nature and extent of social transformation, the question of subjective transformation must be considered.